Un développement urbain durable politisé ou une politique de développement urbain durable ? - Soufiane Boukarta (Cybergeo, 2011)
Since the Rio Summit, the sustainable development has become a part of the international law. The International participation in the subsidized projects related to sustainable development has further strengthened its importance. In the third world countries and Algeria is one of them, “the appropriation” of sustainable development seems to move slowly and in a way that seems so far unclear and ambiguous. We focus on this to shed light on the appropriability of actors at the local level, where the policy makes sense. At first glance, it seems that there is an asymmetric appropriation between policies posted and what is happening locally. Local actors do not seem to be willing to accommodate locally the sustainable development. This article aims to open a debate about this gap between policy as willingness and practice as action locally built.